Compressive strength, splitting tensile strength and water absorption of sago fibre reinforced concrete - Tan, Choon Hong. (Universiti Malaysia Sarawak (UNIMAS), 2017)
Sago fibre is one of the by-products of sago starch production in sago production plant that is usually disposed in landfill. Since the waste fibre generated from sago starch extraction is in a huge amount, it will contribute to environmental problems if not managed well. It had been shown that the application of natural fibre in fibre reinforced concrete is practicable. However, the application of sago fibre in fibre reinforced concrete is yet to be explored and studied. This research presents the strength development and water absorption of plain concrete and sago fibre reinforced concrete. 1.2% of sago fibre by volume is added to the plain concrete to produce the sago fibre reinforced concrete. Slump test was conducted to determine the workability of fresh concrete and the density of hardened concrete is determined in saturated condition. The strength development of concrete was identified from the compressive strength test and splitting tensile strength test. Furthermore, the water absorption characteristic of the concrete was also identified. The workability of fibre reinforced concrete in fresh state is lower than that of plain concrete as control. The fibre reinforced concrete also marked a higher compressive strength development over a curing age of 56 days. This is due to the crack arresting properties of the fibre incorporated in concrete matrix. The splitting tensile strength of fibre reinforced concrete is higher than that of plain concrete over a curing age of 28 days. This is due to the bridging effect of the sago fibre in the concrete matrix. The water absorption of fibre reinforced concrete is also higher than that of plain concrete over a curing age of 56 days.